Estimación de incidencia de problemas estructurales causados por errores de diseño y construcción de instalaciones hidrosanitarias en el Cantón Chambo - Sula Milan, Alex David (2022)
The increase in the demand for housing in the Chambo Canton makes it necessary to build taller buildings where the intervention of various systems becomes necessary to provide the structure with a habitable environment, among them we have the architectural part, the structural part, and the hydro-sanitary systems, which, being of great importance, must be distributed in such a way that they do not affect the structural behavior of the building. This research aims to obtain an estimate of the incidence of structural problems caused by errors in the design and construction of hydro-sanitary facilities in the Chambo canton. Based on a visual inspection, the structures that are affected by this problem in the urban area and the urban expansion zone of the Chambo canton are identified. The field survey was carried out using a predefined table where the structures were classified as affected, unaffected and unidentified. Subsequently, the information was processed using the ArcGIS Software, marking the affected properties thanks to the cadastre provided by GADM de Chambo. The result of the investigation showed that 42% of the structures are affected by the problem, that is, that structural members, both beams and columns, are crossed by hydro sanitary elements. For this reason, it is necessary to recommend that the behavior of the structural members that are affected by the incorporation of pipes within their work area be investigated and how it would affect their behavior in the event of a seismic event.